Optimal exercise dose-response improves health-related quality of life in cancer survivors: a systematic review and Bayesian network meta-analysis of RCTs - Xiong, Zhiyu; Yuan, Yuan; Yang, Yong; Qiu, Bopeng; Bai, Ying; Wang, Tao; Wang, Junyu; Zhang, Lin; Li, Yawen (Frontiers in Oncology, 2024)
ObjectiveCancer survivors often face significant health-related quality of life (HRQoL) challenges. Although exercise has been proven to improve HRQoL in cancer survivors, the optimal dose and intensity of exercise for this population has not been fully determined. Adherence to exercise may vary based on exercise intensity, affecting results. This study explored the dose-response relationship of different exercise types and intensities to better understand their impact on HRQoL in cancer survivors.MethodsWe searched five databases—PubMed, Embase, the Cochrane Library, Web of Science, and Scopus—from their inception until 1 December 2023. Data analysis was performed using R software with the MBNMA and RJAGS packages. Due to combining data from different scales, effect sizes were reported as standardized mean differences (SMD) with 95% credible intervals (95% CrI). The risk of bias was assessed independently by three reviewers using the RoB2 tool.ResultsA total of 48 studies involving 3050 cancer survivors. Across all exercise types, the most beneficial exercise dose was identified to be 850 metabolic equivalents of task (METs)-min/week (SMD: 0.753, 95%Crl: 0.463 to 1.096), with diminishing returns observed beyond 1,100 METs-min/week. Among the various types of exercises, mixed training (MT) emerged as the optimal choice, demonstrating its efficacy at 970 METs-min/week (SMD: 0.883, 95% Crl: 0.455 to 1.345). Aerobic exercise (AE) at a dose of 430 METs-min/week (SMD: 0.681, 95% Crl: 0.206 to 1.099) and resistance training (RT) at 450 METs-min/week (SMD: 0.695, 95% Crl: 0.227 to 1.203) also showed significant benefits. Additionally, mind-body exercises, such as tai chi, qigong, or yoga, exhibited optimal effects at a dose of 390 METs-min/week (SMD: 0.672, 95% Crl: 0.259 to 1.087).ConclusionOur study sheds light on the intricate relationship between exercise interventions and health-related quality of life in cancer survivors, as elucidated through a systematic review and Bayesian network meta-analysis. The identified optimal exercise dose of 850 METs-min/week resulted in a significant improvement in health-related quality of life, underscoring the importance of regular exercise in cancer survivorship. MT emerged as the most effective modality, closely followed by RT, AE, and MBE.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=493328, identifier CRD42024493328.